ChemInform Abstract: Linear and Third Order Nonlinear Optical Properties of LiRbB4O7 Single Crystal. Issue 8 (February 2016) - Sukumar, M.; Babu, R. Ramesh; Ramamurthi, K.
Abstract: A LiRbB4 O7 single crystal is grown by the Czochralski method employing Li2 CO3, H3 BO3, and Rb2 CO3 (Pt crucible, 600 °C, pulling and rotation rate of 0.2‐0.3 mm/h and 8‐15 rpm).